Comparative survey of adult neurogenic sites in adult avian species: an immunohistochemical study - Mazengenya, Pedzisai (My University, 2018)
Adult neurogenesis is a widely accepted and preserved phenomenon throughout the animal kingdom occurring in both invertebrates and vertebrates, including humans. The process has been extensively studied in mammalian vertebrates and comparably less in the class aves. In birds, the process has been studied more so in the song bird brain. The current thesis, investigated putative adult neurogenesis in the brains of seven species of birds from different taxonomic orders exhibiting different behavioural repertoires, particularly determining and localizing the active neurogenic regions, migratory routes of migrating neuroblasts and regions of integration of new neurons. The birds examined in the current thesis belonged to the following taxonomic orders: Columbifomes (domestic pigeons; racing homer and utility carneau pigeons); Psittaciformes (Congo African grey and Timneh grey parrots); Passeriformes (pied crow); Struthioniformes (common ostrich) and Casuariiformes (emu). Free floating immunohistochemical methods against proliferating cell nuclear antigen (PCNA) which labels proliferating cells and doublecortin (DCX) which stains immature neurons were used to determine the regions of cells proliferation, migratory routes of immature neurons and recruitment sites as final destination in the brains of the birds to see if these processes are associated with variations in behavioural repertoires and/or show phylogenetic relations. Results from the current thesis showed that cell proliferation is widespread throughout the brains of all the birds examined, with high levels of cell proliferation in the olfactory bulbs and the subventricular zones (SVZ) of the lateral ventricles in the telencephalon; the SVZ of the lateral ventricle is the primary neurogenic zone contributing new neurons in the adult telencephalon; immature neurons are localised in high density in the olfactory bulb and the subdivisions of the telencephalon, but in low densities in the subtelencephalic regions except in the ratite birds (common ostrich and emu) where moderate densities were observed in the cortex of the cerebellum; the distribution of the immature neurons showed region specificity within the subdivisions of the telencephalon across all species with high densities in the medial and lateral regions of the pallial and subpallial regions, but devoid in the core areas; species-specific distribution of immature neurons was also observed in the hippocampal formations and song control systems of the pied crow and cerebellum of the ratite birds indicating behavioural specialisations and migratory routes of immature neurons were not clearly defined across species except in the ratites birds where three distinct bundles of migrating neuroblasts were observed in the telencephalon. In the majority of the studied birds neuroblasts migrated from the dorsal and ventral poles of the SVZ of the lateral ventricle into the hyperpallium and medial striatum respectively. The wide spread distribution of the proliferating cells and immature neurones in the brains of adult from various taxonomic orders, although in varied extents indicates that adult neurogenesis is a conserved trait in all species of birds and might be important for environmental and behavioural adaptations. In addition, the process might also help to explain phylogenetic relationships of birds along the evolutionary scale. Thus this thesis provides clues to the presence and extent of adult neurogenesis in various species of birds highlighting on possible behavioural repertoires impacted by adult neuronal plasticity.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2018.